Наземные моллюски (Gastropoda, Pulmonata) заповедника Кодры (Молдова) - Байдашников, А.А. (Вестник зоологии, 1993)
Among 53 species, reviewed here under zoogeograhic and ecological viewpoints, numerous are for the first time recorded for Central Moldovian Highland and for Republic of Moldova (Serrulina serrulcita, Balea biplicata, Discus perspectivus, Perforalella dibo thrion, Monachioides vicina, Vitrea diaphana, Oxychilus glaber, Derocercas turcicum). The only condition of niolluskan and concommitant mesofauna protection (especially relic) is a complete reservation regime to be established in Kodras. Serrulina serrulata is suggested to include into the Red Data Book of Moldova and to the European Red List of Endangered Species.